Peroxisome Proliferator-Activated Receptor γ Induces the Expression of Tissue Factor Pathway Inhibitor-1 (TFPI-1) in Human Macrophages. (27th December 2016) - Chinetti-Gbaguidi, G.; Copin, C.; Derudas, B.; Marx, N.; Eechkoute, J.; Staels, B.
Abstract : Tissue factor (TF) is the initiator of the blood coagulation cascade after interaction with the activated factor VII (FVIIa). Moreover, the TF/FVIIa complex also activates intracellular signalling pathways leading to the production of inflammatory cytokines. The TF/FVIIa complex is inhibited by the tissue factor pathway inhibitor-1 (TFPI-1). Peroxisome proliferator-activated receptor gamma (PPAR γ ) is a transcription factor that, together with PPAR α and PPAR β / δ, controls macrophage functions. However, whether PPAR γ activation modulates the expression of TFP1-1 in human macrophages is not known. Here we report that PPAR γ activation increases the expression of TFPI-1 in human macrophages in vitro as well as in vivo in circulating peripheral blood mononuclear cells. The induction of TFPI-1 expression by PPAR γ ligands, an effect shared by the activation of PPAR α and PPAR β / δ, occurs also in proinflammatory M1 and in anti-inflammatory M2 polarized macrophages. As a functional consequence, treatment with PPAR γ ligands significantly reduces the inflammatory response induced by FVIIa, as measured by variations in the IL-8, MMP-2, and MCP-1 expression. These data identify a novel role for PPAR γ in the control of TF the pathway.